KAJIAN LITERATUR NARATIF PENDEKATAN TEORITIS KOMUNIKASI KELUARGA - Runtiko, Agus Ganjar (Jurnal Common, 2021)
Research on family communication is currently finding momentum because of its closeness to human daily life. This paper aims to provide academic resources in the form of theories that can be used in the context of family communication. The research method used is desk research with a literature review approach. The results of the study found that there are several theories that can be used to examine family communication according to the research needs. First, the Family Communication Pattern Theory (FCPT) can be used if the researcher wants to carry out research in the scope that all family members are involved, especially in the scope of the nuclear family. Second, the Family System Theory, which can be used to see the dynamics in the family that involves a larger family scope. Third, Attachment Theory, which tends to see the family as an aspect of communication psychology, namely how to connect attachment styles and communication. The hope of this writing is that it can contribute to science in terms of providing ready-made material for communication science theory so that it can be used by communication researchers according to the context of the research being carried out.